Guide to firewalls and VPNs - Whitman, Michael E. (Course Technology / Cengage Learning, 2012)
Firewalls are among the best-known network security tools in use today, and their critical role in information security continues to grow. However, firewalls are most effective when backed by thoughtful security planning, well-designed security policies, and integrated support from anti-virus software, intrusion detection systems, and related tools. GUIDE TO FIREWALLS AND VPNs, THIRD EDITION explores firewalls in the context of these critical elements, providing an in-depth guide that focuses on both managerial and technical aspects of security. Coverage includes packet filtering, authentication, proxy servers, encryption, bastion hosts, virtual private networks (VPNs), log file maintenance, and intrusion detection systems. The book also features an abundant selection of realistic projects and cases incorporating cutting-edge technology and current trends, giving you a valuable opportunity to hone and apply your knowledge and skills. GUIDE TO FIREWALLS AND VPNs includes new and updated cases and projects, enhanced coverage of network security and VPNs, and information on relevant National Institute of Standards and Technology guidelines used by businesses and information technology professionals nationwide.